Pengaruh Penerapan Fungsi Manajemen Terhadap Peningkatan Mutu Tenaga Pendidik MA Al-Amiriyyah Blokagung Tegalsari Banyuwangi Tahun Pembelajaran 2018/2019 - Nasrulloh, M. Alaika; Hidayati, Nur; Yani, Pitri (Jurnal Manajemen Pendidikan Islam Darussalam, 2019)
This study aims to: 1) To determine the application of management functions in MA al-Amiriyyah Blokagung Academic Year 2018/2019. 2) To find out the quality of the teaching staff at the MA al-Amiriyyah Blokagung Academic Year 2018/2019. 3) To find out whether there is an influence of the application of the management function to the improvement of the quality of the MA al-Amiriyyah Blokagung educators in 2018/2019 Academic Year. 4) To find out how much influence the application of the management function to the improvement of the quality of the MA al-Amiriyyah Blokagung teacher education year 2018/2019. This study uses quantitative descriptive methods with data analysis using simple linear regression. After analyzing the data, it was found that (1) the application of management functions at MA al-Amiriyyah Blokagung was very good. (2) The quality of the teaching staff at MA al-Amiriyyah Blokagung is very good. (3) There is an effect of the application of management functions on improving the quality of MA al-Amiriyyah Blokagung's teaching staff. (4) the influence of the application of management functions on improving the quality of MA al-Amiriyyah Blokagung's teaching staff by 55.5%.